2015
DOI: 10.1155/2015/821061
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavior Evaluation Based on Physiological Parameters among Young Healthy Subjects with Yoga as Intervention

Abstract: Objective. To investigate the effect of yoga practice on cognitive skills, autonomic nervous system, and heart rate variability by analyzing physiological parameters. Methods. The study was conducted on 30 normal young healthy engineering students. They were randomly selected into two groups: yoga group and control group. The yoga group practiced yoga one and half hour per day for six days in a week, for a period of five months. Results. The yoga practising group showed increased α, β, and δ EEG band powers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 31 publications
4
37
1
Order By: Relevance
“…In a randomized controlled trial, the yoga group versus the control group showed reduced work-related stress and a significant increase in heart rate variability (vagal activity) following a 12-week program [146]. In a five-month program (90 min per day 6 days per week) the yoga group versus a control group showed a significant increase in heart rate variability (vagal activity) and a reduction in the LF/HF ratio [147]. The yoga group also showed increased alpha, beta and theta EEG band powers and a reduction in delta band power suggesting enhanced memory and concentration and synchronization of brain activity.…”
Section: Potential Underlying Mechanismsmentioning
confidence: 95%
“…In a randomized controlled trial, the yoga group versus the control group showed reduced work-related stress and a significant increase in heart rate variability (vagal activity) following a 12-week program [146]. In a five-month program (90 min per day 6 days per week) the yoga group versus a control group showed a significant increase in heart rate variability (vagal activity) and a reduction in the LF/HF ratio [147]. The yoga group also showed increased alpha, beta and theta EEG band powers and a reduction in delta band power suggesting enhanced memory and concentration and synchronization of brain activity.…”
Section: Potential Underlying Mechanismsmentioning
confidence: 95%
“…A study also published in 2015 by Nagendra et al investigated the effects of yoga on the cognitive ability, autonomic nervous system and heart rate variability (HRV)-measured by means of electroencephalography (EEG) and echocardiography (ECG) recordings-in engineering students. They found significant improvements in several cognitive functions-including memory, neuronal activity and alertness-and alterations in HRV tending towards parasympathetic dominance [18].…”
Section: Introductionmentioning
confidence: 98%
“…As a general approach, previous studies have tried to link the EEG power in specific bands to HRV measures. Although significant correlations were found for the α (8-12 Hz) [48][49][50][51][52], β (13-30 Hz) [49,50,53] and γ (>30 Hz) bands [53,54], the psychophysiological meaning of such associations is still ill-defined. For instance, complexity of HRV series was used to predict changes in the EEG α band after stress [48].…”
Section: Introductionmentioning
confidence: 99%